1994
DOI: 10.1016/0014-5793(94)01256-3
|View full text |Cite
|
Sign up to set email alerts
|

Is Zn2+ transported by the mitochondrial calcium uniporter?

Abstract: Zinc ions were found to inhibit Ca2' uptake by rat liver mitochondria driven by succinate respiration but not that by a valinomycin-induced membrane potential. Zn'+ at 1 PM or higher concentrations induced a lowering of the membrane potential under the former but not the latter conditions. It is concluded that it is the lowered membrane potential in the presence of Zn" that reduces the rate of respiration-driven Car'. Ruthenium red was found to inhibit the uptake of Zn2+ but had no influence on its action upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 22 publications
2
49
0
Order By: Relevance
“…Internalization of cytosolic Zn 2ϩ into the mitochondrial matrix has not been unequivocally demonstrated. However, indirect evidence was pro- Zn 2ϩ Stimulates ROS Production by LADH (30). Zn 2ϩ inhibition of respiration in isolated, intact mitochondria in a substrate-dependent manner (10) provides further indirect evidence of Zn 2ϩ internalization by mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Internalization of cytosolic Zn 2ϩ into the mitochondrial matrix has not been unequivocally demonstrated. However, indirect evidence was pro- Zn 2ϩ Stimulates ROS Production by LADH (30). Zn 2ϩ inhibition of respiration in isolated, intact mitochondria in a substrate-dependent manner (10) provides further indirect evidence of Zn 2ϩ internalization by mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Zn 2ϩ has been implicated in several mitochondrial changes, such as ion transport (55)(56)(57) and membrane swelling (33,56,58,59). Membrane swelling has been associated with the opening of the mitochondrial permeability transition pore, loss of membrane potential, and uncoupling of respiration (60).…”
Section: Discussionmentioning
confidence: 99%
“…' Brierly and Knight (1967) reported that heart mitochondria accumulated zinc by energy-dependent and by passive processes depending upon the conditions employed; but free Zn + + ions in the range of 100-500 μM was employed in those studies. It has been suggested that free Zn + + ions enter the mitochondria via the calcium uniporter (Saris and Niva, 1994). However those studies were also conducted with unphysiological concentrations of free Zn + + ions.…”
Section: Zinc Trafficking Into Mitochondriamentioning
confidence: 99%